KARAKTERISASI LIPASE TERMOSTABIL (ISOLAT AL96) BERDASARKAN PARAMETER TEMPERATUR DAN pH PADA INDUSTRI MAKANAN - septiani septiani (Lantanida Journal, 2019)
This research aims to produce large amounts of lipase and have high activity so that it can be utilized in the food industry. Method of Research used a thermostable enzyme derived from compost AL96 microorganisms. Qualitative tests are carried out using Thermus media. Extracellular lipase enzyme expressed by AL96 culture at 700C for 17 hours was isolated as much as 1000 mL and the crude extract obtained was deposited by fractionation of ammonium sulfate. After obtaining a fraction of 0-30%; 30 -50% fraction; 50-70% fraction; and 7-90% fraction was then tested for lipase enzyme activity using spectrophotometric techniques and testing of protein content determined by the Bradford method. Results Of research obtaining partial purification using ammonium sulfate into crude enzyme extract from AL96 isolate with a fraction of 50-70% resulted in the highest specific activity of protein 0.018 U / mg. Further analysis of lipase in the 30-50% fraction has the optimum temperature at 65 0C and the fraction of 50-70% has the optimum temperature at 75 0C. Characterization of the optimum pH for 50-70% fraction and 30-50% fraction showed that both fractions had optimum pH 10.